Effect of myocardial protection and perfusion temperature on production of cytokines and nitric oxide during cardiopulmonary bypass - Tavares-Murta,Beatriz Martins (2007)
PURPOSE: To investigate the effects of different conditions used during cardiopulmonary bypass (CPB) surgery on accompanying production of cytokine and nitric oxide (NO). METHODS: Patients undergoing CPB for the first time were prospectively enrolled and divided into two groups according to CPB parameters performed: i) normothermia (36.5-37°C) with blood cardioplegia (NB group, n=10) and ii) hypothermia (29-31°C) with crystalloid cardioplegia (HC group, n=10). Plasma samples obtained following intubation (baseline), during (5 and 30 min) and after (4 and 24 h) CPB were assayed for cytokines (ELISA) and NO metabolites (Griess reaction). RESULTS: Peak concentrations of interleukin (IL)-6 and IL-8 were reached at 4 h post CPB in both groups, but in the HC group those levels increased earlier and persisted for longer (24 h) compared to baseline (P < 0.05). IL-10 levels also increased at 4 h compared to baseline, but only significantly so in the HC group. NO metabolites were reduced in HC group at all time points compared to baseline (P < 0.05), while no significant differences were detected in the NB group. CONCLUSION: The association between increased systemic levels of cytokines and reduced NO production in the HC group suggests that different myocardial protection and/or perfusion temperature used during CPB may contribute to the extent of inflammatory response.